.........................
Anexe:
Răspunsuri la întrebare
Răspuns de
1
3 - √(x² + 3) = x |²
[3 - √(x² + 3)]² = x²
3² - 6√(x² + 3) + x² + 3 = x²
9 - 6√(x² + 3) + 3 = 0
12 - 6√(x² + 3) = 0
6√(x² + 3) = 12
√(x² + 3) = 12/6
√(x² + 3) = 2 |²
x² + 3 = 4
x² = 4 - 3
x² = 1
x = 1
[3 - √(x² + 3)]² = x²
3² - 6√(x² + 3) + x² + 3 = x²
9 - 6√(x² + 3) + 3 = 0
12 - 6√(x² + 3) = 0
6√(x² + 3) = 12
√(x² + 3) = 12/6
√(x² + 3) = 2 |²
x² + 3 = 4
x² = 4 - 3
x² = 1
x = 1
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă